Increasing the resource of agricultural machines - Dudnikov, Anatolii; Dudnikov, Ihor; Dudnyk, Volodymyr; Mykhailichnko, Vladyslav; Burlaka, Oleksii; Kanivets, Oleksander (Technology audit and production reserves, 2021)
The object of research is the technological process of increasing the service life of pointed cultivator shares of tillage machines through the use of a progressive method of vibration hardening. One of the most problematic areas is the inadequate study of the investigated technological process of restoring the working bodies of agricultural machines. In order to gain a deeper understanding of the process of vibration processing of the material of these machine parts during their restoration, it is necessary to conduct further experimental studies. In the course of the study, it has been found that the use of vibration deformation of the surface layer of the material of parts contributes to an increase in their resource. The optimal parameters of vibration hardening of the cutting elements of the cultivator shares of tillage machines have been determined, which makes it possible to increase their durability. The main parameters of vibration hardening are revealed: the vibration amplitude of the processing tool is 0.75 mm; vibration frequency – 1400 min–1; hardening time – 30 s. As a research result, the assessment of the change in linear wear along the width of the cutting element of the cultivator duckfoot of tillage machines was carried out. In cultivators with tines restored by welding angle plates made of 45 steel (GOST 1050-2013, GB 699-88), sormite surfacing and vibration hardening, the linear wear rate by weight of cutting elements is 35–43 % less than in new tines. A study of changes in the wear of the cutting edge of cultivator shares was carried out, which, when restored by welding corner plates made of steel 45 (GOST 1050-2013, GB 699-88), surfacing with sormite and vibration hardening, is 1.57–1.68 times less than in new shares. In comparison with existing technologies, the developed technology provides a reduction in the wear of cutting elements by 10–17 %, in comparison with new ones made of 65G steel (GOST 14959-2016, GB 1222). The coefficient of technical utilization of the cultivator with tines restored according to the developed technology, in comparison with the new ones, is 1.07 times higher.